Mapping structure heterogeneities and visualizing moisture degradation of perovskite films with nano-focus WAXS - Nian Li; Shambhavi Pratap; Volker Körstgens; Sundeep Vema; Lin Song; Suzhe Liang; Anton Davydok; Christina Krywka; Peter Müller-Buschbaum (Nature Communications, 2022)
Understanding the correlation between moisture degradation and structural features of perovskite films is essential to improve their stability. Here, the authors apply nano-focused wide-angle X-ray scattering to map the heterogeneities over several micrometers across lateral and vertical directions.